Corporate social responsibility as a source of competitive advantage: Strategic contradictions in the food industry - Adrian Peretz; Fred Strønen (Contemporary Economics, 2024)
In the eight decades since researchers started to explore the possibility that firms' responsibilities extended beyond the interests of shareholders, research on Corporate Social Responsibility (CSR) has ballooned. The number of calls for more research on a steadily growing number of CSR-related domains has grown in line with the number of calls for businesses to behave responsibly. CSR has become a standard by which firms are measured, and compliance with CSR norms and regulations figures into firms' business decisions. Although many studies suggest that firms can combine profits for shareholders with benefits to stakeholders, the ulti- mate promise of CSR-that behaving responsibly can contribute to competitive advantage-has not been delivered. This may be because the complexities involved in creating competitive advantage require such a combination of singular focus and favorable circumstances that there is no room for competing goals. The main contribution of this paper is to show that even firms that successfully incorporate substantial and profit- able CSR programs into core business activities do not envisage that such programs can contribute to creat- ing competitive advantage. This study examines grocery retail chains that are answering calls for increased responsibility and sustainability by developing profitable food waste reduction programs. Although these sustainability programs increase profits for the retail chains and provide benefits to society, the chains do not see how such programs-or any other CSR initiatives-can contribute to competitive advantage.
Keywords: D21; L21; M14; 330; CSR; waste management; retail industry; competitive advantage